5-HTTLPR polymorphism is linked to neural mechanisms of selective attention in preschoolers from lower socioeconomic status backgrounds. (December 2016) - Isbell, Elif; Stevens, Courtney; Hampton Wray, Amanda; Bell, Theodore; Neville, Helen J.
Highlights: We investigated associations between 5-HTTLPR genotypes and selective attention. Lower SES children aged 3–5 completed an ERP selective attention task. Children with at least one short 5-HTTLPR allele had larger ERP attention effects. The short allele is linked to enhanced neural mechanisms of attention in children. This lays the groundwork for gene-by-environment studies involving cognitive skills. Abstract: While a growing body of research has identified experiential factors associated with differences in selective attention, relatively little is known about the contribution of genetic factors to the skill of sustained selective attention, especially in early childhood. Here, we assessed the association between the serotonin transporter linked polymorphic region (5-HTTLPR) genotypes and the neural mechanisms of selective attention in young children from lower socioeconomic status (SES) backgrounds. Event-related potentials (ERPs) were recorded during a dichotic listening task from 121 children (76 females, aged 40–67 months), who were also genotyped for the short and long allele of 5-HTTLPR. The effect of selective attention was measured as the difference in ERP mean amplitudes elicited by identical probe stimuli embedded in stories when they were attended versus unattended. Compared to children homozygous for the long allele, children who carried at least one copy of the short allele showed larger effects of selective attention on neural processing. These findings link the short allele of the 5-HTTLPR to enhanced neural mechanisms of selective attention and lay the groundwork for future studies of gene-by-environment interactions in the context of key cognitive skills.